Labor market regulations in the context of structural transformation - Priya Ranjan; Rana Hasan; Erik Jan Eleazar (Asian Development Bank (ADB), 2018)
This paper constructs a theoretical model to study labor market regulations in developing countries within the context of structural transformation. When workers are risk averse and the market for insurance against labor income risk is missing, regulations that provide insurance to workers (such as severance payments) are efficiency enhancing and promote structural transformation. However, regulations that simply create barriers to the dismissal of workers not only impede structural transformation, they also end up reducing the welfare of workers. The implications of some other issues like general regulatory burden, weak state capacity, and minimum wage regulations are analyzed as well. The paper provides some empirical evidence broadly consistent with the theoretical results using cross-country data. While dismissal regulations increase the share of informal employment, severance payments to workers do not.
Keywords: J38; J46; O12; O17; O57; 330; dismissal regulations; informal employment; minimum wage; severance payments; structural transformation